The Role of Parenting Interventions in Optimizing School Readiness for Children With Disabilities in Low and Middle Income Settings - Smythe, Tracey; Almasri, Nihad A.; Moreno Angarita, Marisol; Berman, Brad D.; Kraus de Camargo, Olaf; Hadders-Algra, Mijna; Lynch, Paul; Samms-Vaughan, Maureen; Olusanya, Bolajoko O. (Frontiers in Pediatrics, 2022)
Addressing inequity for children with disabilities is enshrined in the UN Convention on the Rights of the Child, the Convention on the Rights of Persons with Disabilities, and the Sustainable Development Goals (SDGs), which include a range of commitments for the provision of disability-inclusive education and health services. Fulfilment of these pledges is important considering that children with disabilities face greater challenges accessing quality education and appropriate health services, and experience worse learning and health outcomes especially in low- and middle-income countries. Urgent action is needed as children with disabilities are being left behind in the ‘thrive and transform’ agenda. Culturally sensitive parenting initiatives must be geared toward ‘school readiness’ for educational inclusion of young children with disabilities. This necessitates that the community, teachers and parents work together with children towards successful developmental and learning outcomes. We make the case for optimising school readiness for children with disabilities by focusing on disability and its determinants within culturally sensitive parenting interventions, and early child development teaching programmes at schools, to better inform parents and teachers and strengthen education systems towards achieving the full intent of SDG 4.2 and global development goals for all.